2012
DOI: 10.1111/j.1538-4616.2012.00535.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Simple Monetary and Fiscal Rules under Limited Asset Market Participation

Abstract: When the central bank is the sole policymaker, the combination of limited asset market participation and consumption habits can have dramatic implications for the optimal monetary policy rule and for stability properties of a business cycle model characterized by price and nominal wage rigidities. In this framework, a simple countercyclical …scal rule plays a twofold role. On the one hand it ensures uniqueness of the rational expectations equilibrium when monetary policy follows a standard Taylor rule. On the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 71 publications
2
21
1
Order By: Relevance
“…Bi and Kumhof find a large gain in welfare from an optimal simple rule which allows for transfers (or tax cuts) targeted to liquidity-constrained consumers to respond aggressively to the tax revenue gap. Subsequent work by Motta and Tirelli (2012) find similar results. In addition, McKay and Reis (2013) find that institutional features of the U.S. transfer system, particularly unemployment insurance and safety-net programs, in the presence of rule-of-thumb consumers, may result in a certain degree of automatic stabilization.…”
Section: Understanding the Stabilizing Effects Of Stabilization Policysupporting
confidence: 74%
“…Bi and Kumhof find a large gain in welfare from an optimal simple rule which allows for transfers (or tax cuts) targeted to liquidity-constrained consumers to respond aggressively to the tax revenue gap. Subsequent work by Motta and Tirelli (2012) find similar results. In addition, McKay and Reis (2013) find that institutional features of the U.S. transfer system, particularly unemployment insurance and safety-net programs, in the presence of rule-of-thumb consumers, may result in a certain degree of automatic stabilization.…”
Section: Understanding the Stabilizing Effects Of Stabilization Policysupporting
confidence: 74%
“…Ascari et al (2011) consider a model without an explicit role for fiscal policy and find that if both prices and wages are sticky, monetary policy should simply stabilize inflation fluctuations even in the presence of RT consumers. Motta and Tirelli (2012) find that introducing both LAMP and consumption habits makes fiscal activisms optimal. In particular, while monetary policy should respond to inflation fluctuations even more strongly than under the representative agent model, fiscal policy should aim at stabilizing nominal income growth.…”
Section: Introductionmentioning
confidence: 93%
“…Furthermore, the fiscal instruments at the disposal of the planner are often limited in number. Motta and Tirelli (2012), for instance, assume that the policymaker can access non-distortionary lump-sum taxes. The present paper shows that optimal fiscal policy aims at reducing fluctuations in income distribution even in the absence of consumption habits, once one allows for capital accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…The problem is certainly relevant in our context where consumption of RT households may be substantially lower than average. Moreover, we found that the combination of LAMP and external-habits-indifferences may cause indeterminacy even for a relatively small share of RT consumers (as in Motta and Tirelli, 2013a). For these reasons we consider the habit-in-ratio specification used in Abel (1988) asset pricing model and in Leeper et al (2009) business cycle model.…”
Section: The Modelmentioning
confidence: 99%